Low and asymmetrical hippocampal glutamate levels in healthy older adults. (20th December 2022) - Roalf, David R; Robinson, Heather; Kesselring, Irena; Jee, Joelle; Mordy, Arianna; Ruparel, Kosha; Meeks, Jacqueline; Wolk, David A.; Nanga, Ravi Prakash Reddy; Gur, Ruben C; Reddy, Ravinder
Abstract: Background: Glutamate (Glu) is a critical molecule in cellular metabolism and the most abundant excitatory neurotransmitter in the brain. Glutamate dysfunction is common in neurodegenerative disorders—patients with Alzheimer's disease (AD) have lower hippocampal glutamate—and likely contributes to age‐related declines in cognitive functioning. The extant literature on age‐related changes in brain Glu is small and all studies have employed proton spectroscopy. Thus, in this investigation we use a novel 7T magnetic resonanace imaging technique, Glutamate Chemical Exchange Saturation Transfer (GluCEST), to compare bilateral hippocampal brain Glu in between healthy old and young adults. Method: Hippocampal GluCEST data were acquired from 14 healthy older adults [HOA; age: 71 (+/‐3)] and 10 young healthy adults [HYA; age: 21 (+/‐3)] using a Siemens 7T Terra. GluCEST data was acquired in axial slice positioned through bilateral hippocampus. Associations between MoCA scores and bilateral hippocampal GluCEST levels were investigated. Result: Bilateral glutamate levels were 7% higher HYA as compared to HOA. HOA showed significant asymmetry (Left>Right) within the hippocampus while GluCEST in HYA were equivalent across hemisphere (t(22)=2.37, p<0.03). Within HOA, higher left hippocampal GluCEST levels were associated with higher performance on the MoCA [r(13)=0.55, p<0.04]. Conclusion: GluCEST appears to be a marker of aging‐related neurological and cognitive change. The present findings are similar to previous findings in AD (Graff‐Radford et al., 2013) Moreover, the left‐right asymmetry in GluCEST aligns with recent translational studies indicating a left‐right dissociation in long‐term memory function, which may be partially mediated by asymmetries in glutamate receptor content (Shipton et al., 2014). This preliminary study is the first to compare GluCEST levels in young and older adults and is the first step towards elucidate age‐related trajectories of glutamatergic alterations and their relationship to clinical and cognitive phenotypes.